A metallographic corrosion method of iridium and a metallographic structure detection method

Through the coordinated cooperation of the use of chloride ion corrosion liquid and AC electrolysis, good corrosion of the iridium metal phase is achieved, the problem of using toxic hydrofluoric acid in the prior art is solved, and the operation safety and environmental friendliness are improved.

CN119756994APending Publication Date: 2025-04-04ITP CO LTD(CN)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411953449.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art inevitably uses toxic hydrofluoric acid when corrosion of iridium metallic samples, resulting in unsafe operation and environmentally harmful and difficult to achieve controllable grain boundary corrosion.

Method used

The chloride ion corrosion solution is used for alternating electrolytic corrosion, and the metal surface is activated by chloride ions and combined with sinusoidal alternating current provides bidirectional periodic pulse current to avoid passivation of the anode surface and the formation of an electric double layer, thereby achieving good corrosion of the iridium metal phase.

Benefits of technology

It realizes clear corrosion of the iridium metal phase, shows obvious grain boundaries, the corrosion process is gentle and controllable, and there is no need to use strongly corrosive components such as hydrofluoric acid, which improves operational safety and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119756994A_ABST
    Figure CN119756994A_ABST
Patent Text Reader

Abstract

The present invention provides an iridium metallographic corrosion method and a metallographic structure detection method. The iridium metallographic corrosion method comprises the following steps: grinding and polishing an iridium sample to obtain an iridium metallographic sample, and subjecting the iridium metallographic sample to AC electrolytic corrosion in a chloride ion corrosion solution to obtain an iridium metallographic corrosion sample. The iridium corrosion method provided by the present invention achieves good corrosion of the iridium metallographic phase by controlling the sample current density within a suitable range through the coordinated cooperation of the chloride ion corrosion solution and the AC electrolysis, with clear grain boundary display, and a mild and controllable corrosion process, without the need to use highly corrosive components such as hydrofluoric acid and nitric acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material analysis, and relates to a metallographic corrosion method, in particular to an iridium metallographic corrosion method and a metallographic structure detection method. Background Art

[0002] The metallographic structure determines the properties of metal materials. Corrosion observation of metallographic samples is an important means of analyzing the microstructure of metal materials.

[0003] At present, for corrosion-resistant metals, metallographic etching is usually performed by adding a highly corrosive mixed acid such as hydrofluoric acid and nitric acid. For example, in the metallographic etching liquid and metallographic etching method disclosed in CN107217264A, CN117702119A, etc., a mixed acid of hydrofluoric acid, nitric acid and other acids is used for metallographic etching. The fluorine ion permeability of hydrofluoric acid is extremely strong and the corrosiveness is extremely strong. The purpose of adding hydrofluoric acid is to enhance the corrosion strength. It is often used in the corrosion liquid of corrosion-resistant metals, but hydrofluoric acid is also very harmful to people and the environment, and is not suitable for general use. Therefore, it is urgent to explore a method of having a good corrosion effect on corrosion-resistant metals and not using a corrosion liquid with toxic and dangerous components.

[0004] Iridium metal has very stable chemical properties and is one of the most corrosion-resistant metals. Iridium is extremely chemically stable to acids and is insoluble in acids. Only sponge-like iridium will slowly dissolve in hot aqua regia. If iridium is in a dense state, it cannot be corroded even by boiling aqua regia. Because iridium has extremely strong corrosion resistance, it is difficult to observe its metallographic structure by controlling the corrosion of grain boundaries.

[0005] CN106119851A discloses a metallographic etchant for displaying iridium grain boundaries and a preparation method thereof. The metallographic etchant is composed of hydrofluoric acid, sodium chloride and water. The iridium metallographic sample is corroded at a voltage of 3-6V and then metallographic observation is performed.

[0006] "Study on the Microstructure and Room-temperature Tensile Fracture Mechanism of Iridium Sheets" (Liu Yi et al., "Precious Metals", Vol. 36, No. 3, pp. 42-48, August 2015) discloses a corrosion medium for a metallographic sample of iridium sheets, which is a saturated sodium chloride solution with hydrochloric acid and hydrofluoric acid added, and the voltage is controlled at 10V for corrosion.

[0007] It can be seen that in the prior art, hydrofluoric acid is inevitably used for the corrosion of iridium metallographic samples, and its main corrosion effect is also produced by hydrofluoric acid.

[0008] Therefore, it is necessary to provide a safe, easy-to-operate and efficient iridium metallographic etching method. Summary of the invention

[0009] The purpose of the present invention is to provide a metallographic corrosion method and a metallographic structure detection method of iridium, which adopts a corrosion liquid with safe and simple components, forms a mild and stable corrosion process through alternating current electrolysis, achieves a good corrosion effect of iridium metallographic phase, and is used for iridium metallographic structure detection.

[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides an iridium metallographic etching method, the iridium metallographic etching method comprising the following steps:

[0012] After grinding and polishing the iridium sample, an iridium metallographic sample is obtained, and the iridium metallographic sample is subjected to alternating current electrolytic corrosion in a chloride ion corrosive solution to obtain an iridium metallographic corrosion sample.

[0013] The iridium metallographic corrosion method provided by the present invention uses chloride ion corrosive liquid to perform alternating current electrolytic corrosion. During the electrolysis process, chloride ions can avoid the passivation of the anode metal surface, play a role in activating corrosion, keep the metal surface in an activated state or change it into an activated state, realize the grain boundary corrosion of iridium, do not need to use highly corrosive and dangerous components such as hydrofluoric acid, nitric acid or H2O2, solve the problem of operational safety, and avoid excessive corrosion; alternating current is used to provide the electrode with a bidirectional periodically changing pulse current instead of unidirectional direct current, eliminate the electrolyte layer of high-concentration salt formed by metal cations and anions in the electrolyte near the anode surface, that is, the so-called "viscous layer" or double electric layer, avoid the surface passivation of the iridium anode generated by using direct current and the influence of the double electric layer on the ion mass transfer process in the electrolyte, improve the corrosion efficiency, and facilitate uniform corrosion. Through the coordinated cooperation of chloride ion corrosive liquid and alternating current electrolysis, good corrosion of iridium can be achieved, and the surface of the sample shows clear grain boundaries.

[0014] Preferably, the chloride ion concentration in the chloride ion etching solution is 4-10mol / L, for example, it can be 4mol / L, 4.5mol / L, 5mol / L, 5.5mol / L, 6mol / L, 6.5mol / L, 7mol / L, 7.5mol / L, 8mol / L, 8.5mol / L, 9mol / L, 9.5mol / L or 10mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the chloride ion etching solution comprises NaCl and HCl.

[0016] The chloride ion etching solution provided by the present invention uses NaCl and HCl as the solute components of the etching solution. The function of NaCl is to provide sodium ions and chloride ions, increase the conductivity of the electrolyte and activate the metal surface. The function of HCl is to reduce the overpotential of hydrogen evolution and provide chloride ions, so that hydrogen gas at the cathode is more easily precipitated, and energy consumption is reduced. At the same time, the addition of HCl can avoid the increase of the pH value of the electrolyte during the electrolysis process, thereby avoiding the formation of Ir(OH)4 precipitation in the electrolyte to affect the subsequent electrolysis. Through the combination of NaCl and HCl, the stable corrosion of the iridium phase is achieved economically and efficiently.

[0017] Preferably, the molar ratio of NaCl to HCl is (1-5):1, for example, 1:1, 2:1, 3:1, 4:1 or 5:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the alternating current of the alternating current electrolytic corrosion is a sinusoidal alternating current.

[0019] In the present invention, the frequency of the sinusoidal alternating current is not limited, and generally 50-500 Hz is adopted for easy operation and cost saving.

[0020] Preferably, the current density of the AC electrolytic corrosion is 1-5 mA / mm 2 , for example, it can be 1mA / mm 2 , 1.5mA / mm 2 , 2mA / mm 2 , 2.5mA / mm 2 、3mA / mm 2 、3.5mA / mm 2 , 4mA / mm 2 , 4.5mA / mm 2 or 5mA / mm 2 , but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0021] In the present invention, the calculation area of ​​the current is measured based on the corrosion area of ​​the iridium metallographic sample.

[0022] In the present invention, electrolytic current density is the key indicator to be pursued. In order to obtain the current density within the preferred range, different electrolyte concentrations, different electrode cross-sectional areas, and different pH values ​​will lead to different overall impedances, and thus the required AC electrolytic corrosion voltages will be different. Preferably, the AC electrolytic corrosion voltage does not exceed 5V.

[0023] Preferably, the corrosion time of the AC electrolytic corrosion is 10-40 min, for example, it can be 10 min, 15 min, 20 min, 25 min, 30 min, 35 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the grinding process comprises: grinding the iridium sample from 400 mesh to above 2000 mesh in order of sandpaper mesh from low to high.

[0025] Preferably, the step-by-step grinding method includes: according to the grinding sequence, the grit of the sandpaper for the next grinding stage is 1.5-2 times that of the sandpaper for the previous grinding stage, and the directions of the two adjacent grinding stages are perpendicular to each other.

[0026] Preferably, the polishing is performed using a polishing flannel cloth.

[0027] As a preferred technical solution of the iridium metallographic etching method provided by the present invention, the iridium metallographic etching method comprises the following steps:

[0028] (1) Grind the cut or mounted iridium sample step by step starting from 400 mesh using sandpaper in ascending order of mesh size, with the directions of two adjacent grinding steps being perpendicular to each other, and finally grind to a size of 2000 mesh or above;

[0029] (2) polishing the ground iridium sample with a polishing flannel to obtain an iridium metallographic sample;

[0030] (3) using the iridium metallographic sample as one end electrode to perform alternating current electrolytic corrosion in a chloride ion corrosion solution, wherein the chloride ion corrosion solution comprises NaCl and HCl, wherein the concentration of chloride ions is 4-10 mol / L; the alternating current of the alternating current electrolytic corrosion is a sinusoidal alternating current, and the effective current of the alternating current electrolytic corrosion is 1-5 mA / mm 2 The calculation area of ​​the effective current is based on the corrosion area of ​​the iridium metallographic sample, and the corrosion time of the AC electrolytic corrosion is 10-40min;

[0031] (4) After the AC electrolytic corrosion is completed, the corroded iridium metallographic sample is rinsed with running water and then dried to obtain an iridium metallographic corrosion sample.

[0032] In a second aspect, the present invention provides a method for metallographic structure detection of iridium, wherein the metallographic structure detection method is performed using an iridium metallographic corrosion sample prepared by the iridium metallographic corrosion method described in the first aspect.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The iridium corrosion method provided by the present invention controls the sample electrolysis current density through the coordinated cooperation of chloride ion corrosion solution and alternating current electrolysis, thereby achieving good corrosion of the iridium metal phase, clear grain boundary display, mild and controllable corrosion process, and no need to use highly corrosive components such as hydrofluoric acid and nitric acid. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a metallographic image of the iridium metallographic corrosion sample provided in Example 1;

[0036] Figure 2 is a metallographic image of the iridium metallographic corrosion sample provided in Example 2;

[0037] Figure 3 is a metallographic image of an iridium metallographic corrosion sample provided in Example 3;

[0038] Figure 4 is a metallographic image of an iridium metallographic corrosion sample provided in Example 4;

[0039] Figure 5 is a metallographic image of an iridium metallographic corrosion sample provided in Example 5;

[0040] Figure 6 is a metallographic image of an iridium metallographic corrosion sample provided in Example 6;

[0041] Figure 7 is a metallographic image of an iridium metallographic corrosion sample provided in Example 7;

[0042] Figure 8 is a metallographic image of an iridium metallographic corrosion sample provided in Example 8;

[0043] Fig. 9 This is the metallographic image of the iridium metallographic corrosion sample provided in Example 9. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] In order to clearly illustrate the technical solution of the present invention, in a specific implementation manner, a metallographic corrosion sample is observed under a microscope to obtain a metallographic diagram.

[0046] Example 1

[0047] This embodiment provides an iridium metallographic etching method, which comprises the following steps:

[0048] (1) Grind the cut iridium rod sample with a diameter of 7 mm. Grind it step by step in the order of 240 mesh, 400 mesh, 800 mesh, 1200 mesh, and 2000 mesh. The directions of the two adjacent grinding steps are perpendicular to each other by 90°. Grind until the grinding marks of the previous sandpaper are completely removed.

[0049] (2) polishing the ground iridium rod sample with a polishing flannel cloth to obtain an iridium metallographic sample;

[0050] (3) preparing a corrosion solution, mixing 20 g of NaCl with 10 mL of 12 mol / L hydrochloric acid, and diluting the volume to 100 mL with distilled water to obtain a chloride ion corrosion solution, wherein the chloride ion concentration in the chloride ion corrosion solution is 4.6 mol / L, the NaCl concentration is 3.4 mol / L, the HCl concentration is 1.2 mol / L, and the molar ratio of NaCl to HCl is 2.83:1;

[0051] Then, in the electrolytic cell, the corrosion liquid is used as the electrolyte, and the iridium metallographic sample is used as one end electrode to connect to the sinusoidal AC power supply controlled by the transformer for electrolytic corrosion. Two multimeters are used to monitor the AC voltage at both ends of the electrolytic cell and the AC current flowing through the electrolytic cell at the same time. The AC current is controlled by adjusting the AC voltage to stabilize the AC current at 160mA. At this time, the actual current density of the corrosion surface of the iridium rod is 4.16mA / mm 2 At this time, the corresponding electrolytic corrosion AC voltage is 3.4V, the frequency is 50Hz, and the electrolytic corrosion time is 35min;

[0052] (4) After the corrosion is completed, the metallographic sample is rinsed with running water and then dried to obtain a metallographic corrosion sample of iridium.

[0053] In this embodiment, the metallographic image of the metallographic corrosion sample is as follows: Figure 1 As shown, clear iridium grain boundaries and cracking along the grain boundaries can be seen. The grain boundaries are clearly displayed and the corrosion effect is obvious.

[0054] Example 2

[0055] This embodiment provides an iridium metallographic etching method, which comprises the following steps:

[0056] (1) Cut the iridium bar into iridium samples with a cross-section size of 4 mm × 5 mm and grind them in the order of 240 mesh, 400 mesh, 800 mesh, 1200 mesh, and 2000 mesh. The directions of the two adjacent grinding steps are perpendicular to each other by 90°. Grind until the grinding marks of the previous sandpaper are completely removed.

[0057] (2) polishing the ground iridium rod sample with a polishing flannel cloth to obtain an iridium metallographic sample;

[0058] (3) preparing a corrosion solution by mixing 25 g of NaCl with 5 mL of concentrated hydrochloric acid having a concentration of 11.6 mol / L, and diluting the volume to 100 mL with distilled water to obtain a chloride ion corrosion solution having a chloride ion concentration of 4.85 mol / L, a NaCl concentration of 4.27 mol / L, and a HCl concentration of 0.58 mol / L, and a ratio of NaCl to HCl of 7.36:1;

[0059] Then, in the electrolytic cell, the corrosion liquid is used as the electrolyte, and the iridium metallographic sample is used as one electrode to connect to the sinusoidal AC power supply controlled by the transformer. Two multimeters are used to monitor the AC voltage at both ends of the electrolytic cell and the AC current flowing through the electrolytic cell. The AC current is controlled by adjusting the AC voltage to stabilize the AC current at 30mA. At this time, the actual current density of the corrosion surface of the iridium rod is 1.5mA / mm 2 At this time, the corresponding electrolytic corrosion AC voltage is 1.5V, the frequency is 500Hz, and the electrolytic corrosion time is 10min;

[0060] (4) After the corrosion is completed, the metallographic sample is rinsed with running water and then dried to obtain a metallographic corrosion sample of iridium.

[0061] In this embodiment, the metallographic image of the obtained metallographic corrosion sample is as follows: Figure 2 As shown, clear grain boundaries can be seen, the grain boundaries are clearly displayed, and the corrosion effect is obvious.

[0062] Example 3

[0063] This embodiment provides an iridium metallographic etching method. Compared with Example 1, the sample cross-section size is the same. In the etching solution, NaCl and HCl are used in equal proportions to make the chloride ion concentration 10 mol / L. The AC current is controlled by adjusting the AC voltage to stabilize the AC current at 160 mA. The actual current density of the iridium rod corrosion surface is 4.16 mA / mm 2 At this time, the corresponding electrolytic corrosion AC voltage is 2.6V, the frequency is 50Hz, and the electrolytic corrosion time is 35min.

[0064] In this embodiment, the metallographic image of the obtained metallographic corrosion sample is as follows: Figure 3 As shown, clear iridium grain boundaries can be seen and the corrosion effect is obvious.

[0065] Example 4

[0066] This embodiment provides an iridium metallographic corrosion method. Compared with Example 2, the current density of the electrolytic corrosion is controlled to be 3 mA / mm 2 , the rest are the same as in Example 1.

[0067] In this embodiment, the metallographic image of the obtained metallographic corrosion sample is as follows: Figure 4As shown, clear iridium grain boundaries can be seen and the corrosion effect is obvious.

[0068] Example 5

[0069] This embodiment provides an iridium metallographic etching method. Compared with Embodiment 1, only NaCl is added under the condition of maintaining the same chloride ion concentration in the etching solution, and the rest is the same as Embodiment 1.

[0070] In this embodiment, the metallographic image of the obtained metallographic corrosion sample is as follows: Figure 5 As shown, a layer of precipitate is formed at the grains and grain boundaries, which affects the metallographic observation.

[0071] Example 6

[0072] This embodiment provides an iridium metallographic etching method. Compared with Embodiment 2, only HCl is added under the condition of maintaining the same chloride ion concentration in the etching solution, and the rest is the same as Embodiment 2.

[0073] In this embodiment, the metallographic image of the obtained metallographic corrosion sample is as follows: Figure 6 As shown, clear iridium grain boundaries can be seen and the corrosion effect is obvious.

[0074] Example 7

[0075] This embodiment provides an iridium metallographic etching method. Compared with Embodiment 1, the concentration of NaCl in the etching solution is replaced by KCl, and the rest is the same as Embodiment 1.

[0076] In this embodiment, the metallographic image of the obtained metallographic corrosion sample is as follows: Figure 7 As shown, some precipitates are formed at the grain boundaries and fractures, affecting the metallographic observation.

[0077] Example 8

[0078] This embodiment provides an iridium metallographic etching method. Compared with Example 2, equal proportions of NaCl and HCl are used in the etching solution to make the chloride ion concentration 3 mol / L, and the rest is the same as Example 2.

[0079] In this embodiment, the metallographic image of the obtained metallographic corrosion sample is as follows: Figure 8 As shown, it can be seen that the iridium grain boundary corrosion is shallow, some grain boundaries have not been corroded, and the corrosion effect is not clear enough.

[0080] Example 9

[0081] This embodiment provides an iridium metallographic corrosion method. Compared with Example 1, the current density of the electrolytic corrosion is controlled to be 6 mA / mm 2 , the rest are the same as in Example 1.

[0082] In this embodiment, the metallographic image of the obtained metallographic corrosion sample is as follows: Fig. 9 As shown, it can be seen that the grain boundaries and grains are slightly over-corroded, which affects the metallographic observation.

[0083] The corrosion effects of the embodiments and comparative examples are summarized in Table 1.

[0084] Table 1

[0085] Corrosion Effects and Description Example 1 The grain boundary is clear and the corrosion effect is obvious Example 2 The grain boundary is clear and the corrosion effect is obvious Example 3 The grain boundary is clear and the corrosion effect is obvious Example 4 The grain boundary is clear and the corrosion effect is obvious Example 5 A layer of precipitate is formed on the grains and grain boundaries, which affects the metallographic observation. Example 6 The grain boundary is clear and the corrosion effect is obvious Example 7 Some precipitates are generated at the grain boundaries and fractures, affecting metallographic observation Example 8 The grain boundary corrosion is shallow, some grain boundaries are not corroded, and the corrosion effect is not clear enough Example 9 There is a little excessive corrosion on the grain boundaries and grains, which affects the metallographic observation

[0086] It can be seen from Table 1 and the accompanying drawings that the iridium metallographic etching method provided by the present invention can obtain an iridium metallographic phase diagram with clear grain boundaries and a good etching effect. Compared with Example 1, in Examples 5-9, after changing the components of the etching solution, the chloride ion concentration and the corrosion current density, the etching effect is significantly worse, affecting the metallographic observation effect.

[0087] In summary, the iridium corrosion method provided by the present invention controls the sample electrolysis current density through the coordinated cooperation of chloride ion etching solution and AC electrolysis, achieves good corrosion of the iridium metal phase, shows clear grain boundaries, and the corrosion process is mild and controllable, without the need to use highly corrosive components such as hydrofluoric acid and nitric acid.

[0088] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. An iridium metallographic etching method, characterized in that: The iridium metallographic etching method comprises the following steps: After grinding and polishing the iridium sample, an iridium metallographic sample is obtained, and the iridium metallographic sample is subjected to alternating current electrolytic corrosion in a chloride ion corrosive solution to obtain an iridium metallographic corrosion sample.

2. The iridium metallographic etching method according to claim 1, characterized in that: The chloride ion concentration in the chloride ion etching solution is 4-10 mol / L.

3. The iridium metallographic etching method according to claim 1 or 2, characterized in that: The chloride ion etching solution comprises NaCl and HCl.

4. The iridium metallographic etching method according to claim 3, characterized in that: The molar ratio of NaCl to HCl is (1-5):

1.

5. The iridium metallographic etching method according to any one of claims 1 to 4, characterized in that: The alternating current of the alternating current electrolytic corrosion is a sinusoidal alternating current.

6. The iridium metallographic etching method according to any one of claims 1 to 5, characterized in that: The current density of the AC electrolytic corrosion is 1-5 mA / mm 2 , the calculation area of ​​the current is based on the corrosion area of ​​the iridium metallographic sample; Preferably, the AC power frequency of the AC electrolytic corrosion is 50-500 Hz.

7. The iridium metallographic etching method according to any one of claims 1 to 6, characterized in that: The corrosion time of the AC electrolytic corrosion is 10-40 minutes.

8. The iridium metallographic etching method according to any one of claims 1 to 7, characterized in that: The grinding process includes: grinding the iridium sample from 400 mesh to more than 2000 mesh in order of sandpaper mesh from low to high; Preferably, the step-by-step grinding method includes: according to the grinding sequence, the grit of the sandpaper for the next grinding stage is 1.5-2 times the grit of the sandpaper for the previous grinding stage, and the directions of the two adjacent grinding stages are perpendicular to each other; Preferably, the polishing is performed using a polishing flannel cloth.

9. The iridium metallographic etching method according to any one of claims 1 to 8, characterized in that: The iridium metallographic etching method comprises the following steps: (1) Grind the cut or mounted iridium sample step by step starting from 400 mesh using sandpaper in ascending order of grit, with the directions of two adjacent levels of grinding being perpendicular to each other, and finally grind to above 2000 mesh; (2) polishing the ground iridium sample with a polishing flannel to obtain an iridium metallographic sample; (3) using the iridium metallographic sample as one end electrode to perform alternating current electrolytic corrosion in a chloride ion corrosion solution, wherein the chloride ion corrosion solution comprises NaCl and HCl, wherein the concentration of chloride ions is 4-10 mol / L; the alternating current of the alternating current electrolytic corrosion is a sinusoidal alternating current, and the effective current of the alternating current electrolytic corrosion is 1-5 mA / mm 2 The calculation area of ​​the effective current is based on the corrosion area of ​​the iridium metallographic sample, and the corrosion time of the AC electrolytic corrosion is 10-40min; (4) After the AC electrolytic corrosion is completed, the corroded iridium metallographic sample is rinsed with running water and then dried to obtain an iridium metallographic corrosion sample.

10. A method for detecting metallographic structure of iridium, characterized in that: The metallographic structure detection method is carried out using an iridium metallographic corrosion sample prepared by the iridium metallographic corrosion method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Metallographic corrosive agent showing iridium crystal boundary and preparation method thereof

    CN106119851A

  • Zirconium base alloy phase corrosion liquid and metal phase corrosion method

    CN107217264A

  • Metallographic etchant for high-entropy alloy, preparation method of metallographic etchant and metallographic etchant method

    CN117702119A